Regulation of the Director General of Islamic Guidance on Marriage of Husband during Wife's Iddah Period: An Effort to Develop Family Law in Indonesia - Miftahudin, M. (SMART: Journal of Sharia, Traditon, and Modernity, 2023)
This research examines the husband's marriage during his wife's iddah period at the Office of Religious Affairs in Lampung Province. This type of research is field research, which is conducted at the KUA throughout Lampung Province, as a sample of Bandar Lampung City, Metro City and East Lampung Regency. Data sources in this research are primary and secondary data sources. Data analysis in this research uses qualitative methods and uses mashlahah theory. The result of the study is that the Circular Letter of the Director General of Islamic Guidance Number P-005/DJ.III/HK.00.7/10/2021 concerning Marriage of Husband in Wife's Iddah Period, is a regulation that regulates the prevention of husbands who want to marry during their wife's iddah period. The existence of this prevention is an effort to create balance between men and women in iddah arrangements, this will have an impact on the value of gender justice and create benefits between couples. Then by seeing that the existence of male iddah aims at gender justice, and kemashlahatan, it needs to be studied further to be regulated in legislation. The position of Circular Letter of the Director General of Islamic Guidance Number P-005/DJ.III/HK.00.7/10/2021 concerning Marriage during the Wife's Iddah Period has the status of a government policy, so according to the researcher's analysis, there should be a follow-up regulation to the legislative stage so that it becomes the status of a law, which can bind generally and widely, and has a higher legal force than a circular letter.Keyword: Marriage, Husband, Iddah Period, Wife, Lampung Province